Optimization of thermoelectric performance by varying thermoelectric height / Siti Fadzillah Nurain Sidi Omar - Sidi Omar, Siti Fadzillah Nurain (College of Built Environment, 2023)
Global population growth and rapid pace of industrialization is increasing, therefore people facing energy supply depletion and environmental pollution.